Achievements and perspectives on anaerobic co-digestion of food waste and sewage sludge for biogas production - Mohd. Ali, Ainoor Mariana; Mansor, Mariatul Fadzillah; Alam, Md. Zahangir (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Biogas is an economical and environmental friendly renewable energy which can be produced by anaerobic digestion (AD). This biochemical method convert organic compounds (mainly from wastes) into a sustainable source of energy. Anaerobic co-digestion (AcoD) is a method combining more than one substrates to resolve the difficulties faced in a single substrate AD system. Solid wastes increases as the population increase so do the urbanization and industrial industries. Food waste and sewage sludge are the examples of one of the solid wastes. Co-digesting of both substrates may improve process stabilization to increase biogas production and overcome the nutrients imbalance. Thus, anaerobic co-digestion has been recognized as a technology that could provide a clean renewable energy source and helps reduce the landfill problem. This objective of this paper is to investigate the recent achievements and perspectives on interaction of co-digestion between food waste and sewage sludge to improve biogas production. This may provide valuable information on the optimization of combinations of substrates: food waste and sewage sludge and prediction of bioreactor performance.